2015
DOI: 10.1021/ef502768w
|View full text |Cite
|
Sign up to set email alerts
|

Combustion and NO Emission of Shenmu Char in a 2 MW Circulating Fluidized Bed

Abstract: The combustion and NO emission characteristics of Shenmu coal and char were investigated with a thermogravimetry−mass spectrometry (TG−MS) system and on a pilot platform of a 2 MW circulating fluidized bed (CFB), respectively. Unlike Shenmu coal, the disadvantages of Shenmu char combustion include late ignition, poor combustion stability, and poor burnout. Despite its well-developed pore structure, there is less volatile content and more carbon crystal for Shenmu char, resulting in lower combustion reactivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…The surface morphology of OS and OS chars from pyrolysis in the tube furnace reactor is shown in Figure , analyzed by scanning electron microscopy (SEM). The surface of OS was smooth with a dense texture while the surface of OS char was rough with well-developed pore structure formed during pyrolysis . Volatiles of OS were released during OS pyrolysis from the inside of the OS particles, causing formation of pores on the surface of particles and the increase of specific surface area.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The surface morphology of OS and OS chars from pyrolysis in the tube furnace reactor is shown in Figure , analyzed by scanning electron microscopy (SEM). The surface of OS was smooth with a dense texture while the surface of OS char was rough with well-developed pore structure formed during pyrolysis . Volatiles of OS were released during OS pyrolysis from the inside of the OS particles, causing formation of pores on the surface of particles and the increase of specific surface area.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The circulating fluidized bed (CFB) boiler has a de-NO x advantage over the pulverized coal boiler. Traditional CFB combustion has difficulty reaching ultralow NO x emission standards. Tourunen et al . found that NO x emissions from CFB were even more sensitive to oxygen concentration rather than combustion temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they investigated the coal pyrolysis using model compounds and a synthetic coal by TG/MS/FTIR [7] and proved that synthetic coal can be very useful for the study of the reaction mechanisms that involve nitrogen during coal pyrolysis and combustion. Gong et al [8,9] studied the combustion and NO emission of Shenmu char with a TG-MS system and found that the combustion of Shenmu char was problematic due to late ignition, poor combustion stability, and poor burnout compared with Shenmu coal. Wang et al [10] used TG/MS/FTIR system to study the pyrolysis of five coals.…”
Section: Introductionmentioning
confidence: 99%